Cultural Processes : A Social Psychological Perspective - Leung, Angela K.-y.; Chiu, Chi-yue; Hong, Ying-yi (Cambridge : Cambridge University Press, 2010)
With the rapid growth of knowledge concerning ethnic and national group differences in human behaviors in the last two decades, researchers are increasingly curious as to why, how, and when such differences surface. The field is ready to leapfrog from a descriptive science of group differences to a science of cultural processes. The goal of this book is to lay the theoretical foundation for this exciting development by proposing an original process model of culture. This new perspective discusses and extends contemporary social psychological theories of social cognition and social motivation to explain why culture matters in human psychology. We view culture as a loose network of imperfectly shared knowledge representations for coordinating social transactions. As such, culture serves different adaptive functions important for individuals' goal pursuits. Furthermore, with the increasingly globalized and hyper-connected multicultural space, much can be revealed about how different cultural traditions come into contact.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).